Tidal Effects on the Surface Water Cooling Northeast of Hainan Island, South China Sea. Issue 10 (28th September 2020) - Li, Yineng; Curchitser, Enrique N.; Wang, Jia; Peng, Shiqiu
Abstract: Using a 3‐D high‐resolution ocean model, this paper explores the mechanisms that cause surface and subsurface water cooling northeast of Hainan Island during summer. Results show that two cooling centers in the regions east of Wenchang city and east of the Qiongzhou Strait occur when tides are included in the model. The cooling is primarily caused by large‐scale changes in the circulation in the northwestern South China Sea (SCS) through anomalous horizontal pressure gradients caused by inhomogeneous tidal mixing between the near‐shore and off‐shore regions. East of Wenchang city, the offshore tidal currents induce upwelling that brings the near‐bottom cold water to the subsurface. For the region east of the Qiongzhou Strait, the tidally induced westward anomalous currents suppress the warm water transport from Qiongzhou Strait, resulting in a compensating intrusion of cold water from surrounding regions. In addition to the large‐scale circulation changes, the local tidal mixing also contributes to the subsurface water cooling east of the Qiongzhou Strait by mixing near‐bottom cold water with subsurface waters. Interannually, the cooling weakens or intensifies during different (cold or warm) phases of the El Niño–Southern Oscillation (ENSO) events. This is attributed to variability in surface forcings and large‐scale circulation associated with different phases of ENSO leading to changes in stratification, which changes the tidally induced horizontal pressure gradient in the northwestern SCS. Plain Language Summary: The surface water cooling around the eastern and northern coast of Hainan Island is one of the strongest in the South China Sea (SCS). During summer, strong surface water cooling occurs northeast of the island, which is associated with tidal effects. Variable tidal mixing between the coastal region and the open ocean changes the pressure gradient, which results in significant changes in the circulation in the northwestern SCS leading to cooling of the surface waters. On the interannual scale, the sea water cooling induced by tides northeast of Hainan Island weakens (enhances) during the cold (warm) phases of El Niño–Southern Oscillation (ENSO) events. Key Points: Two surface cooler water centers occur in the regions east of Wenchang city and east of the Qiongzhou Strait in summer The inhomogeneous tidal mixing between the coastal and open ocean changes the circulations in the northwestern SCS On the interannual scale, the cooling induced by tides weakens during La Niña years, while significantly enhances during El Niño years